Identifikasi Candida Albicans pada Urine Ibu Hamil yang Berkunjung Di RSUD Labuang Baji Makassar - Nurwahidah Fa'al Santri (Jurnal Media Laboran, 2017)
Candida albicans is a single cell that is round to oval, and multiply by shoots. The presence of Candida as a normal flora in the female genital tract and the increase in pH in pregnant women.The purpose of this study was to identify Candida albicans in the urine of pregnant women who visited RSUD Labuang Baji Makassar. Type of research is laboratory observation using 7 samples.The results of this study are presented in the form of tables and accompanied by narrative so that the results of identification of Candida albicans in the urine of pregnant women who visited the hospitals Labuang Baji Makassar.The result of the research showed that there were 2 samples which showed positive Candida albicans with 28.6% percentage and 5 samples showed negative not found Candida albicans with percentage of 71,4%.It is recommended for pregnant women to maintain sanitation of environmental hygiene, because the main factor causing vaginal Cadidiosis is hygiene problem.